Health literacy and motivation to change health behavior among cardiovascular patients - Hossein Ghalavand; Abdolahad Nabiolahi; Sirous Panahi (BMC Cardiovascular Disorders)
Abstract Introduction Today, cardiovascular diseases (CVDs) have become increasingly prevalent in various societies. Having an adequate level of health literacy and necessary motivation to modify high-risk behaviors are among the key factors influencing the improvement of patient conditions. The present study investigates the relationship between health literacy and motivation to change health behavior among patients with CVDs. Methodology This is a cross-sectional, correlational research. The research population consists of 190 patients with CVDs and a history of hospitalization, who are randomly selected. Health literacy questionnaire and Health Behavior Motivation Scale were used for data collection. The data were analyzed using SPSS 26.0, and descriptive statistics of mean, standard deviation and Pearson’s correlation coefficient. Results 189 cardiovascular patients participated in this study. The mean health literacy scores of patients with CVDs were 23.91, 15.42, 27.38, 15.59 and 46.39 in terms of access, reading skills, understanding, appraisal and application of health information, respectively. Scores for motivation to change health behaviors between CVDs patients revealed means for autonomous motivation were 3.67, for controlled motivation stands at 3.48, and for the probability rating assigned by physicians were 4.06. Considering the significance level of Sig > 0.05, except for understanding health information (f = 2.962, Sig = 0.021), no significant correlation was found between health literacy dimensions and patients’ age. The age variable was not correlated with any of the dimensions of motivation to change patients’ behavior. Moreover, no significant difference was observed between patients’ educational level and their health literacy and motivation for change health behavior dimensions scores (Sig > 0.05). There was no significant relationship between sex and dimensions of health literacy and motivation for health behavior change (Sig > 0.05). Furthermore, a significant correlation was found between patients’ scores in five dimensions of health literacy and motivation for health behavior change (r = 0.154, Sig = 0.034). Conclusion Considering the undesirable level of health literacy among patients with CVDs and a strong correlation between levels of health literacy and motivation for health behavior change, it is recommended that health literacy improvement programs must be developed by health-related institutions through various innovative educational interventions in different in-person and online settings.